The Mediation Effect of Peripheral Biomarkers of Calcium Metabolism and Chronotypes in Bipolar Disorder Psychopathology - Renato de Filippis; Martina D’Angelo; Elvira Anna Carbone; Pasquale De Fazio; Luca Steardo (Metabolites, 2022)
Calcium (Ca++) metabolism may be impaired in several psychiatric diseases. We hypothesize that calcium imbalance might also correlate with a specific chronotype and could be recognized as a marker of illness severity in bipolar disorder (BD). We aimed to (1) identify the association between calcium imbalance and a specific chronotype in a cohort of BD patients, and (2) test the mediation role of high parathyroid hormone (PTH) levels towards a specific chronotype and illness severity in BD patients. Patients’ socio-demographic and clinical characteristics were collected with an ad-hoc schedule. We administered the Hamilton Depression Rating Scale (HAM-D), the Hamilton Rating Scale for Anxiety (HAM-A), the Young Mania Rating Scale (YMRS), and the Morningness Eveningness Questionnaire (MEQ). 100 patients affected by BD were recruited. The Kruskal-Wallis test showed a significant difference between the three MEQ groups in PTH levels (p < 0.001) and vitamin D levels (p = 0.048) but not in Ca++ levels (p = 0.426). Dwass-Steel-Critchlow-Fligner Pairwise analyses performed concerning three MEQ groups revealed significantly higher scores on PTH levels in MEQ-E subjects compared to MEQ-M and MEQ-I (in both cases, p < 0.001). No differences emerged between calcium levels among the three chronotypes. The mediation analysis has shown that elevated PTH levels are directly influenced by more severe HAM-A, HAM-D, and YMRS scores. MEQ-E could be a marker related to BD and predispose to various factors influencing mood symptoms. The combination of vitamin D therapy in MEQ-E may help to improve prognosis in this subtype of patients affected by BD.